Independensi Kekuasaan Kehakiman Dalam Menjatuhkan Putusan Ditinjau Dari Perspektif Undang-Undang Sebagai Perjanjian - Negara, Dharma Setiawan; Susilo, Erwin (Faculty of Law, Universitas Gadjah Mada, 2025)
Abstract Laws (UU) are understood as the manifestation of an agreement between the people, represented by the legislative body (House of Representatives), and the government, represented by the executive body. In a democratic system, the process of forming laws reflects the principles of deliberation and consensus, which aim to create a social, national, and state order. However, the role of the judicial branch in upholding justice is often reduced to merely enforcing laws. Regardless, judges are directly accountable to God under the principle of ‘Justice Based on the Almighty God’ in carrying their duties. This places the judicial power in a unique position, not only as an enforcer of laws but also as an interpreter of justice that must be independent from the influence of the executive and legislative branches. In this context, a fundamental challenge arises: how can judges uphold true justice when laws, as products of agreements between the executive and legislative branches, do not always reflect the substantive values of justice expected by society? Therefore, judicial independence is essential to ensure that decisions are not merely an implementation of the text of the law, but also reflect the justice that exists in society. The principle of checks and balances is not merely about the division of power, but also about how the judicial branch can fulfil its role as an independent guardian of justice in a legal context that is often biased towards political and economic interests. Abstrak Undang-Undang (UU) dipahami sebagai manifestasi perjanjian antara rakyat yang diwakili oleh lembaga legislatif (Dewan Perwakilan Rakyat) dan pemerintah yang diwakili oleh lembaga eksekutif. Dalam sistem demokrasi, proses pembentukan UU mencerminkan prinsip musyawarah dan kesepakatan yang bertujuan untuk menciptakan tata kehidupan bermasyarakat, berbangsa, dan bernegara. Namun, peran kekuasaan kehakiman (Yudisial) dalam menegakkan keadilan sering kali tereduksi menjadi sekadar penerap undang-undang, padahal dalam menjalankan tugasnya, hakim bertanggung jawab langsung kepada Tuhan dengan prinsip